The Effect of Product Quality on Consumer Loyalty Mediated by Customer Satisfaction: Evidence from Persib Bandung Official Store Merchandise - Bayu Fauzan, Nayandra Adi; Dhameria, Vita (Jurnal Manajemen, 2026)
This study aims to examine how product quality shapes consumer loyalty, with consumer satisfaction functioning as a mediating variable among buyers of merchandise from the Persib Bandung Official Store. The research applies a quantitative approach grounded in a positivist paradigm, ensuring that the analytical process produces objective and measurable findings. A total of 102 respondents, all users of official Persib merchandise residing in Bandung, were selected through purposive sampling because they met the criteria relevant to the study’s objectives. Data were collected using a Likert-scale questionnaire designed to capture consumer perceptions systematically. Once the data were obtained, several analytical procedures were performed, including validity and reliability tests, linear regression analysis, and the Sobel test to assess the mediating role of consumer satisfaction in strengthening the relationship between product quality and loyalty. The results indicate that product quality has a positive and significant influence on consumer satisfaction and directly enhances consumer loyalty. Furthermore, consumer satisfaction serves as an important factor that reinforces the impact of product quality on loyalty, demonstrating its role as an effective mediator. These findings highlight that maintaining high product quality is a key strategy for retaining consumers. When merchandise is perceived to be of good quality, consumers tend to feel more satisfied and remain loyal. Therefore, management must consistently uphold strong quality standards to build and sustain long-term relationships with Persib supporters.